2011
DOI: 10.1016/j.jcrs.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of postoperative use of hydrogel ocular bandage and collagen corneal shield for wound protection and patient tolerability after cataract surgery

Abstract: No author has a financial or proprietary interest in any material or method mentioned. Additional disclosures are found in the footnotes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…Results of a prospective study performed specifically to evaluate postoperative pain following cataract surgery reported that approximately one third of patients undergoing cataract surgery report ocular pain during the first 4 postoperative hours, with a quarter of these patients experiencing moderate to severe pain 16. The study also reported that over half of patients experienced postoperative eye symptoms, such as foreign body sensation, pruritus, and irritation, which are often interpreted as ocular findings rather than pain by ophthalmologists 17. As such, given the variable differences associated with each individual’s personal definition of pain and pain severity, the incidence of pain following cataract surgery may be higher than currently reported.…”
Section: Introductionmentioning
confidence: 99%
“…Results of a prospective study performed specifically to evaluate postoperative pain following cataract surgery reported that approximately one third of patients undergoing cataract surgery report ocular pain during the first 4 postoperative hours, with a quarter of these patients experiencing moderate to severe pain 16. The study also reported that over half of patients experienced postoperative eye symptoms, such as foreign body sensation, pruritus, and irritation, which are often interpreted as ocular findings rather than pain by ophthalmologists 17. As such, given the variable differences associated with each individual’s personal definition of pain and pain severity, the incidence of pain following cataract surgery may be higher than currently reported.…”
Section: Introductionmentioning
confidence: 99%
“…A synthetic corneal bandage has many advantages over biologically derived products in terms of reproducibility of its properties and overcoming the need to use animal derived materials or an allogeneic graft. [13][14][15] An ideal bandage contact lens should be transparent, have a high water content, have suffi cient mechanical properties for handling and be antimicrobial. This study developed poly-ε-lysine (pεK)-based Supporting Information) demonstrated a reduction as the chain length of the fatty acid increased.…”
Section: Doi: 101002/adhm201600258mentioning
confidence: 99%
“…The recent clinical trial referenced previously by Dell and colleagues evaluated the safety and efficacy of the hydrogel bandage 12. This prospective randomized controlled clinical study of over 400 patients showed that the device was well tolerated when placed over a cataract incision.…”
Section: Discussionmentioning
confidence: 99%
“…This was a post-hoc analysis performed on a subset of data from a controlled, prospective, randomized, parallel-group multicenter study (n = 420) comparing the ReSure Adherent Ocular Bandage (Ocular Therapeutix, Inc) with the Oasis 24-hour Soft Shield ® Collagen Corneal Shield (Oasis Medical, Glendora, CA, USA) for protection and relief of pain and discomfort following cataract surgery 12. The current analysis included all the hydrogel bandage patients (n = 310) from the original study (except for six patients who received sutures), which comprised 40 patients who did not undergo stromal hydration during surgery and 270 who did receive hydration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation